An 85%-efficiency reconfigurable multiphase switched capacitor DC-DC converter utilizing frequency, switch size, and interleaving scaling techniques. (September 2017) - Mohammed, Shady A.; Dogan, Hakan; Ozgun, Mehmet Tamer
Abstract: A high efficiency all-CMOS switched-capacitor DC-DC converter (SC DC-DC) with frequency, switch size and interleaving scaling is proposed in order to achieve high efficiency for wireless sensors and internet of things (IOTs) applications. According to the output load current, decision making unit adjusts the frequency, switch size and number of interleavers to match the required current profile and reach steady state. 4-equally-phased clocks are utilized in the design of the SC DC-DC converter. The converter is implemented in 65 nm CMOS process with a peak efficiency of 85% at 600 μ A load current. It can supply output current ranging from 20 μ A to 5 mA with efficiency higher than 75%. The converter can be configured into 3 different gain topologies to support nominal output voltages of 1.1 V, 1.65 V and 2.2 V, from a 3.3 V input supply. Total area of the converter is 0.725 mm 2 .